Paleoseismic and geomorphologic evidence of recent tectonic activity of the Pozohondo Fault (Betic Cordillera, SE Spain) - Rodríguez-Pascua, M.A.; Pérez-López, R.; Garduño-Monroy, V.H.; Giner-Robles, J.L.; Silva, P.G.; Perucha-Atienza, M.A.; Hernández-Madrigal, V.M.; Bischoff, J. (Journal of Iberian Geology, 2012)
Instrumental and historical seismicity in the Albacete province (External Prebetic Zone) has been scarcely recorded. However, major strike-slip faults showing NW-SE trending provide geomorphologic and paleoseismic evidence of recent tectonic activity (Late Pleistocene to Present). Moreover, these faults are consistently well oriented under the present stress tensor and therefore, they can trigger earthquakes of magnitude greater than M6, according to the lengths of surface ruptures and active segments recognized in fieldwork. Present landscape nearby the village of Hellin (SE of Albacete) is determined by the recent activity of the Pozohondo Fault (FPH), a NW-SE right-lateral fault with 90 km in length. In this study, we have calculated the Late Quaternary tectonic sliprate of the FPH from geomorphological, sedimentological, archaeoseimological, and paleoseismological approaches. All of these data suggest that the FPH runs with a minimum slip-rate of 0.1 mm/yr during the last 100 kyrs (Upper Pleistocene-Holocene). In addition, we have recognized the last two major paleoearthquakes associated to this fault. Magnitudes of these paleoearthquakes were gretarer than M6 and their recurrence intervals ranged from 6600 to 8600 yrs for the seismic cycle of FPH. The last earthquake was dated between the 1st and 6th centuries, though two earthquakes could be interpreted in this wide time interval, one at the FPH and other from a far field source. Results obtained here, suggest an increasing of the tectonic activity of the Pozohondo Fault during the last 10,000 yrs.